2020
DOI: 10.1149/1945-7111/ab729c
|View full text |Cite
|
Sign up to set email alerts
|

Editors’ Choice—Critical Review—A Critical Review of Solid State Gas Sensors

Abstract: Solid state gas sensors are a core enabling technology to a range of measurement applications including industrial, safety, and environmental monitoring. The technology associated with solid-state gas sensors has evolved in recent years with advances in materials, and improvements in processing and miniaturization. In this review, we examine the state-of-the-art of solid state gas sensors with the goal of understanding the core technology and approaches, various sensor design methods to provide targeted functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
105
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(107 citation statements)
references
References 291 publications
(373 reference statements)
0
105
0
2
Order By: Relevance
“…Such low-cost nodes rely on solid-state chemical sensors for gaseous air pollution monitoring, a class of electronic devices that has been investigated and developed since the 1960s [28][29][30]; these sensors also use relatively less popular low-cost PM sensors (LCPMS). This review focuses on this latter class of sensors, which represents a new frontier in research and industrial development, with new products being continuously proposed and investigated (briefly summarized in Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Such low-cost nodes rely on solid-state chemical sensors for gaseous air pollution monitoring, a class of electronic devices that has been investigated and developed since the 1960s [28][29][30]; these sensors also use relatively less popular low-cost PM sensors (LCPMS). This review focuses on this latter class of sensors, which represents a new frontier in research and industrial development, with new products being continuously proposed and investigated (briefly summarized in Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…184 This effect is believed to be caused by the charge transfer between gas molecules and the polymer or the polymer lm's swelling. 185 This sensing response has intensively increased motivation to develop high sensitive and selective chemical sensors by tailoring the compounds of different organic polymers with functionalised CNTs.…”
Section: Functionalised Cnts In Chemical Sensormentioning
confidence: 99%
“…Wong et al have reviewed the sensing behavior of different CPs as chemiresistive gas sensors and also explained the targeted characteristics that makes the particular CP appropriate for selected gas [198]. Hunter et al have gone over the solid state gas sensors and indicated the oxidation (or doping) plays a crucial role for CP based chemiresistive gas sensors [199]. In addition to doping (or oxidation-reduction), which modifies charge carrier density, other processes can also substantially tailor the electrical conductivity of CPs and lead to alteration in chemiresistive gas sensing.…”
Section: Chemiresistive Gas Sensingmentioning
confidence: 99%